The antivirus hacker's handbook - Koret, Joxean; Bachaalany, Elias (Indianapolis, IN : John Wiley & Sons, Inc., 2015)
"The Antivirus Hacker's handbook shows you how to hack your own system's defenses to discover its weaknesses, so you can apply the appropriate extra protections to keep you network locked up tight."-- Back cover.
Antivirus basics -- Introduction to antivirus software -- Revere-engineering the core -- The plug-ins system -- Understanding antivirus signatures -- The update system -- Antivirus software evasion -- Evading signatures -- Evading scanners -- Evading heuristic engines -- Identifying the attack surface -- Denial of service -- Analysis and exploitation -- Static analysis -- Dynamic analysis -- Local exploitation -- Remote exploitation -- Current trends and recommendations -- Current trends in antivirus protection -- Recommendations and the possible future.
Includes index.
Online resource; title from PDF title page (EBSCO, viewed August 26, 2015).
Keywords: Computer security -- Handbooks, manuals, etc; Computer networks -- Security measures -- Handbooks, manuals, etc; Computer networks -- Access control; COMPUTERS -- Security -- General; Computer networks -- Access control; Computer networks -- Security measures; Computer security; Electronic books; Handbooks and manuals; Handbooks and manuals